Kelainan Sistem Lakrimal Pada Anak - Atikah Landani; Rani Himayani (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2020)
Introductions: The lacrimal system consists of various glands in producing tears and drainage systems. Epiphora, or excessive tears, is a problem that occurs in children, baby or infants. Discussions: The most frequent etiology of this disorder is nasolacrimal duct obstruction. The most frequent abnormalities are defects or blockages in the drainage system, blocked nasolacrimal ducts. Most of the evidence supports conservative management in this case, examinations are conducted for those who fail to resolve at the age of one year. There are several other conditions, some of which can be serious, which can cause a lot of tears. Infections of the eyelids and conjunctiva, foreign bodies that have not been found, and congenital glaucoma are some conditions that must be ruled out when there are children who experience excessive tears. Conclusions: Proper diagnosis and management of the lacrimal system in children will get a better prognosis Keywords: Children, diagnosis, infant, lacrimal, tears